Study Of The Impact Of Regulatory Framework And Bank Initiatives On The Adoption Of Internet Banking In Malaysia, Singapore And Hong Kong - Tan, Swee Ho (2007)
The motivation for this study is the belief that the poor response to Internet banking in Malaysia springs from an inadequate Regulatory Framework for customer protection and the lack of initiatives on the part of the banks in promoting this new delivery channel. In an attempt to find support for this belief, data was also collected from two other countries in the Asia Pacific region namely Singapore and Hong Kong, which are relatively more developed than Malaysia.